Glycemic Status and Lipid Profiles Changes among the Incidentally Diagnosed Fatty Liver Patients - Islam, Md Atiqul; Khan, Ashraf Uddin; Yusuf, Md Abdullah; Nasrin, Shahana; Nabi, Mohammadun; Rowshon, AHM (Journal of National Institute of Neurosciences Bangladesh, 2017)
Background: Fatty liver disease is common condition. Objective: The purpose of the present study was to see the glycemic status and lipid profiles changes among the incidentally diagnosed fatty liver patients. Methodology: This was an observational descriptive study conducted in the Department of Gastroenterology at Shaheed Suhrawardy Medical College & Hospital, Dhaka, Bangladesh from the duration of January 2010 to July 2010 for a period of six (6) months. Seventy patients attending indoor or outdoor of Shaheed Suhrawardy Medical College & Hospital Dhaka, diagnosed ultrasonographically as fatty liver who were met the inclusion and exclusion criteria were recruited. Those subjects who were presented at the outdoor and/or indoor in the hospital for different health problems and were diagnosed as fatty liver on the basis of USG findings were included for this study. Patients of fatty liver diagnosed incidentally by ultrasound, performed for other purposes were planned for study. Blood samples were taken for analysis of risk factors after completing the physical examinations. Result: A total number of 70 patients were recruited for this study. Among the study population, 48 (68.57%) were between 20-50 years of age, 6 (8.57%) were less than 20 years and 16 (22.85%) were more than 50 years. Regarding Glycemic status, 15(21.42%) cases were Diabetic, 25(35.71%) cases had impaired glucose tolerance and 30(42.85%) cases had normal blood sugar. Regarding dyslipidaemia, 51(72.85%) cases had high triglyceride level (>150 mg/dl); 42(60%) cases had hypercholesterimea (>200 mg/dl); decreased HDL (<40 mg/dl) in 37 (52.85%) cases and increased LDL (>150 mg/dl) in 21(44.28%) cases. Conclusion: In conclusion the abnormal gycemic status and dyslipidemia is present in the incidentally diagnosed fatty liver patients. Journal of National Institute of Neurosciences Bangladesh, 2016; 2(1): 26-29